Spodoptera frugiperda population structure and influence of farmers’ practices on gut biodiversity for sustainable management of the pest in Kenya - Ndung’u, Kiarie E.; Khamis, Fathiya M.; Ajene, Inusa J.; Mbogo, Kevin O.; Akutse, Komivi S. (Frontiers in Ecology and Evolution, 2023)
Fall armyworm (FAW), Spodoptera frugiperda, is a highly polyphagous pest that recently invaded Kenya, among other African countries. Information on the pest's genetic diversity and mechanisms conferring insecticide resistance, in addition to farmers' knowledge and perceptions on the applicable mitigation measures, inform the development of sustainable management strategies. Therefore, this study collected cross-sectional data from 800 farmers in Kenya and documented their knowledge and perceptions on FAW and factors influencing their choice of FAW control methods. Additionally, we identified the strains present in 8 counties in Kenya using the mitochondrial Cytochrome Oxidase sub-unit I (mt COI) gene, and correlated pesticide use to gut microbiome diversity via 16S rRNA metagenomics to investigate the probable contribution of gut bacteria towards insecticide resistance evolution. All farmers reported FAW infestations, and 24% reported limited and total non-response of FAW to insecticides. Fall armyworm rice-strain and corn-strain were detected ravaging corn fields. However, the corn-strain revealed higher microbial diversity than the rice-strain. Furthermore, pathogenic bacterial genera were elevated in the insect gut in both corn and rice strains after chemical-treatments. Insecticide-endosymbiont interactions should be further explored, and farmers’ training on effective alternative pest control methods is recommended.